Performance comparison of ultrasonic-assisted and magnetic stirred absorption methods for CO2 separation - Shokrollahi, F.
Chemical absorption is the most matured and preferred separation process which is extensively used for CO2 removal from natural gas. The current contactor systems used in the absorption process suffer from several drawbacks including excessive footprint, operating, and maintenance issues. Ultrasonic irradiation is a new alternative technique to assist the CO2 absorption process without the aforementioned limitations. Thus, the aim of this paper is elucidating the potential of the ultrasonic-assisted CO2 absorption system. To achieve this, the performance of the ultrasonic-assisted system was compared to that of the conventional stirring method. Two different solvents with dissimilar reaction mechanisms were chosen. The first part of the experiments was conducted in the ultrasonic-assisted batch vessel, while the second part was accomplished in the stirred batch cell. The parameters including ultrasonic power, ultrasonic frequency, stirring speed, and initial feed pressure were 18 W, 1.7 MHz, 500 rpm, and 11 bar, respectively. Besides, the operating temperature and the concentration were chosen based on the standard operating condition for each solvent. The mass transfer coefficient was calculated using the dynamic pressure-step method. The results revealed that in comparison with the stirring method, the ultrasonic-assisted absorption system significantly enhanced the CO2 absorption process at similar operating conditions. By using ultrasonic irradiation, the volumetric absorption coefficient increased almost three times for MDEA and nearly six times for MEA. In the latter, this improvement can be related to the physical effect of the ultrasound. However, for the slow kinetic solvents, this improvement might be attributed to the chemical effect of the ultrasound.